Key indicators towards the implementation of green government procurement in Malaysia - Musa N.D.; Buniamin S.; Johari N.H.; Ahmad N.; Rauf F.H.A.; Rashid A.A. (2023)
Green issue is considered as one of the worldwide issues. Many countries such as the United Kingdom, Japan and European Union countries have been actively adopting the sustainable green living concept in their normal lives. Since government is considered as the main purchaser in a country, it represents a large proportion of total public spending in both developed and developing countries. One of the initiatives that already been taken in Malaysia is the implementation of green government procurement (GGP). It has been recognized as an effective tool in minimizing the environmental impacts and can be determined as the government's commitments in sustaining the environment that can be emulated by the society as a whole. However, there is no specific policy, regulation and legal framework that has been implemented in regards to GGP since GGP is a very new concept in Malaysia. GGP has been outlined in Chapter 6 in 10th Malaysian Plan under valuing the nation's environment endowment and the New Economic Model under ensuring sustainability of growth. This research is undertaken due to there is no specific guideline or framework that can be used or referred by the procurement officers in implementing GGP practices in their organizations by using the proposed model. Three main indicators that been involved are familiarity with policies, organisational initiatives and supplier availability that leads to the implementation of the GGP practices in the organization. These indicators hopefully will be useful for the regulators and policy makers, statutory bodies, government linked companies (GLCs) and suppliers in managing the GGP practices. IDOSI Publications, 2013.